It Takes a Village: The Multifaceted Immune Response to Mycobacterium tuberculosis Infection and Vaccine-Induced Immunity - Larsen, Sasha E.; Williams, Brittany D.; Rais, Maham; Coler, Rhea N.; Baldwin, Susan L. (Frontiers in Immunology, 2022)
Despite co-evolving with humans for centuries and being intensely studied for decades, the immune correlates of protection against Mycobacterium tuberculosis (Mtb) have yet to be fully defined. This lapse in understanding is a major lag in the pipeline for evaluating and advancing efficacious vaccine candidates. While CD4+ T helper 1 (TH1) pro-inflammatory responses have a significant role in controlling Mtb infection, the historically narrow focus on this cell population may have eclipsed the characterization of other requisite arms of the immune system. Over the last decade the tuberculosis (TB) research community has intentionally and intensely increased the breadth of investigation of other immune players. Here, we review mechanistic preclinical studies as well as clinical anecdotes that suggest the degree to which different cell types, such as NK cells, CD8+ T cells, gamma delta T cells, and B cells, influence infection or disease prevention. Additionally, we categorically outline the observed role each major cell type plays in vaccine-induced immunity, including Mycobacterium bovis bacillus Calmette-Guérin (BCG). Novel vaccine candidates advancing through either the preclinical or clinical pipeline leverage different platforms (e.g. protein + adjuvant, vector-based, nucleic acid-based) to purposefully elicit complex immune responses and we review those design rationales and results to-date. The better we as a community understand the essential composition, magnitude, timing and trafficking of immune responses against Mtb the closer we are to reducing the severe disease burden and toll on human health inflicted by TB globally.